Electronic Word of Mouth and Brand Image on Customer Decisions - Lusiah Lusiah; Lili Suryati (DINASTI RESEARCH, 2022)
This study aims to examine the effect of Electronic Word of Mouth and Brand Image on Customer Decisions. This study uses explanatory quantitative research on 50star hotelin West Sumatra with 150 respondents processed using the SEM-PLS approach. The results of the study indicate that Electronic Word of Mouth directly influences Customer DecisionsStar Hotel in West Sumatra and Brand Image directly influence Customer DecisionsStar Hotel in Jakarta.